Dubrovin equations and integrable systems on hyperelliptic curves - Gesztesy, Fritz; Holden, Helge (MATHEMATICA SCANDINAVICA, 2002)
We introduce the most general version of Dubrovin-type equations for divisors on a hyperelliptic curve K_g of arbitrary genus gN, and provide a new argument for linearizing the corresponding completely integrable flows. Detailed applications to completely integrable systems, including the KdV, AKNS, Toda, and the combined sine-Gordon and mKdV hierarchies, are made. These investigations uncover a new principle for 1+1-dimensional integrable soliton equations in the sense that the Dubrovin equations, combined with appropriate trace formulas, encode all hierarchies of soliton equations associated with hyperelliptic curves. In other words, completely integrable hierarchies of soliton equations determine Dubrovin equations and associated trace formulas and, vice versa, Dubrovin-type equations combined with trace formulas permit the construction of hierarchies of soliton equations.